The Effect of E-Module with Zakat Context on Students' Mathematical Communication Skills on Numbers - Salsabila, Maimanah; Johar, Rahmah; Ikhsan, M. (Kreano, Jurnal Matematika Kreatif-Inovatif, 2025)
The limitations of mathematical communication skills and the lack of experience in applying mathematics to everyday life, including worship-related problems, result in poor mathematical communication skills and a lack of student independence. Applying E-modules in the context of zakat can be one solution to address this problem. This study aimed to examine whether the mathematical communication skills of students using an e-module with a zakat context on numbers were better than those of students not using the e-module. This quantitative study employed a posttest only control group design. The sample consisted of two classes from a junior high school in Banda Aceh, Indonesia, selected using a simple random sampling technique. The samples consisted of 65 students, divided into an experimental group of 33 students and a control group of 32 students. Data collection was conducted by administering a test of mathematical communication skills. The results show that the mathematical communication skills of students using the e-module with the zakat context were better than those of their counterparts. The interactive e-modules support student independence and develop students' mathematical communication skills. Further research should be conducted to support the development of more effective and user-friendly online learning platforms for mathematics learning. Abstrak Keterbatasan penyelesaian masalah kemampuan komunikasi matematis dan kurangnya pengalaman dalam menyatakan matematika di kehidupan sehari-hari termasuk masalah ibadah menyebabkan rendahnya kemampuan komunikasi matematis dan kurangnya kemandirian siswa. Salah satusolusi yang dapat dilakukan guru adalah menerapkan E-modul dengan konteks zakat. Tujuan dari penelitian ini adalah untuk mengkaji apakah kemampuan komunikasi matematis siswa yang menggunakan e-modul dengan konteks zakat pada materi bilangan lebih baik dibandingkan dengan siswa yang tidak menggunakan e-modul. Penelitian ini merupakan penelitian kuantitatif menggunakan posttest only control group design. Sampel dalam penelitian ini terdiri atas dua kelas dari salah satu SMP di Banda Aceh yang dipilih melalui teknik simple random sampling. Sampel penelitian ini terdiri atas 65 siswa, yaitu 33 siswa pada kelas eksperimen dan 32 siswa pada kelas kontrol. Teknik pengumpulan data menggunakan tes kemampuan komunikasi matematis yang diperoleh melalui posttest. Hasil penelitian menunjukkan bahwa kemampuan komunikasi matematis siswa yang menggunakan E-modul dengan konteks zakat lebih baik dari siswa yang tidak menggunakan e-modul. Oleh karena itu, E-modul dengan konteks zakat merupakan sebuah media pembelajaran interaktif untuk menunjang kemandirian siswa serta membangun kemampuan komunikasi matematis siswa. Penelitian selanjutnya diharapkan mampu memberikan kontribusi dalam dunia pendidikan terkait pengembangan platform pembelajaran online yang lebih efektif dan mudah digunakan.